THE EFFECT OF THE ULOS LEARNING MODEL ON CRITICAL THINKING SKILLS OF GRADE XI SMA NEGERI 2 PEMATANGSIANTAR IN THE 2025/2026 ACADEMIC YEAR - Lestari Maria Esterlina Silalahi; Apriani Sijabat; Ady Frenly Simanullang (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to investigate the effect of the ULOS learning model on the critical thinking skills of eleventh-grade students at SMA Negeri 2 Pematangsiantar in the 2025/2026 academic year. The ULOS learning model, which stands for Use the Essential Question, Let’s Design Project and Do It, Observe Result Project and Discussion, Summarize and Reflect, is a project-based learning approach grounded in constructivist theory and integrated with local cultural values. This model encourages students to develop critical thinking and creativity through contextual problem-solving and collaborative learning experiences. The research employed a quantitative quasi-experimental design with a Pretest-Posttest Control Group Design. The population consisted of all eleventh-grade science students, and two classes were selected as samples using a simple random sampling technique. The experimental class was taught using the ULOS learning model, while the control class received conventional instruction. Data were collected using essay tests designed to measure five indicators of critical thinking skills—providing simple explanations, building basic skills, drawing conclusions, providing further explanations, and setting strategies and tactics. The collected data were analyzed using normality, homogeneity, and independent sample t-tests. The findings revealed a significant difference between the experimental and control groups, indicating that the ULOS learning model had a positive effect on students’ critical thinking skills in physics learning. The implementation of ULOS created an active, collaborative, and culturally meaningful learning environment that enhanced students’ analytical and reflective abilities. The study concludes that the ULOS learning model is an effective pedagogical approach for improving students’ critical thinking skills and promoting culturally responsive education within the framework of the Merdeka Curriculum. The results suggest that teachers should adopt innovative, student-centered learning models such as ULOS to foster higher-order thinking and cultural awareness in science education.